2015
DOI: 10.1007/s10529-015-1916-z
|View full text |Cite
|
Sign up to set email alerts
|

A new methodological approach to estimation of IgA1 and IgA2 content in human serum using recombinant IgA1 protease from Neisseria meningitidis

Abstract: The proposed method is economical and reliable and can be used for evaluation of IgA1 and IgA2 in clinical laboratories or for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Experimental confirmation of the protective activity of IgA1 protease is shown in a small number of works. In a series of works [64][65][66][67][68][69][70][71][72][73][74] in animal experiments, it was shown that native IgA1 protease isolated from a live virulent culture of N. meningitidis serogroup A, as well as recombinant IgA1 proteases of N. meningitidis serogroup B in active or mutant forms, and some truncated analogs of these proteins have high immunogenic and protective activity.…”
Section: Iga1 Protease and Its Fragments As A Basis For The Creation Of Therapeutic And Preventive Agentsmentioning
confidence: 99%
“…Experimental confirmation of the protective activity of IgA1 protease is shown in a small number of works. In a series of works [64][65][66][67][68][69][70][71][72][73][74] in animal experiments, it was shown that native IgA1 protease isolated from a live virulent culture of N. meningitidis serogroup A, as well as recombinant IgA1 proteases of N. meningitidis serogroup B in active or mutant forms, and some truncated analogs of these proteins have high immunogenic and protective activity.…”
Section: Iga1 Protease and Its Fragments As A Basis For The Creation Of Therapeutic And Preventive Agentsmentioning
confidence: 99%